Measuring the activity of European and African Countries using Social Accounting Matrices - Santos, Susana (2017)
Economic models at the micro, meso and macro levels presuppose the existence of consistent databases that make it possible to quantify the activity of enterprises, sectors, regions, countries or continents. Such models can also be important aids in the policy decision process, since they permit the construction of scenarios resulting from the adoption of policy measures and the consequent changes that they introduce. When consistent with the United Nations System of National Accounts (SNA), the Social Accounting Matrix (SAM) can include all the nominal flows of the measured part of the economy, at the level of both production and the institutions, and therefore satisfies these requirements. Thus, in its numerical version, a SAM constitutes a database and provides a snapshot of the measured reality at a certain moment, whereas its possible algebraic versions, i.e. models that are based upon it, permit the construction of the above-mentioned scenarios. The possibility and usefulness of constructing SAMs for African countries consistent with the SNA will be examined and experimented. The SAM’s basic structure and consistency within the whole system will be studied, as well as any possible disaggregations, extensions, aggregates, indicators and balances that can be calculated. Other aspects beyond that basic structure will also be examined in order to show to what extent the SAM is capable of covering parts of the economy that are not covered by the SNA.